2014
DOI: 10.1139/cjpp-2013-0274
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the neuroprotective effects of ginsenosides Rg1 and Rb1 extracted fromPanax notoginsengagainst cerebral ischemia

Abstract: Panax notoginseng, a traditional Chinese medicine, has been used for thousands of years to treat ischemic patients. More than 20 saponin components have been isolated from P. notoginseng root and identified chemically. However, these different chemical components have different roles. In this study we compared the neuroprotective mechanisms of ginsenosides Rg1, Rb1, Rg1/Rb1, and panax notoginsenoside (PNS) against injuries caused by cerebral ischemia-reperfusion (I/R). Our results show that all of these treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 33 publications
0
59
1
Order By: Relevance
“…In the tMCAO mice model, we demonstrated that PNS effectively lead to a decrease in the infarct volume, histological damage, and neurological deficits after I/R, which contradicted previous studies [11, 12]. In addition, we revealed, in quite a direct way, that PNS alleviated the microvascular disturbances, including leukocyte adhesion and albumin leakage.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…In the tMCAO mice model, we demonstrated that PNS effectively lead to a decrease in the infarct volume, histological damage, and neurological deficits after I/R, which contradicted previous studies [11, 12]. In addition, we revealed, in quite a direct way, that PNS alleviated the microvascular disturbances, including leukocyte adhesion and albumin leakage.…”
Section: Discussioncontrasting
confidence: 52%
“…I/R injury was inflicted through transient middle cerebral artery occlusion (tMCAO), which has been widely used in previous studies [11, 12]. Mice were separated into four groups: the Sham group, ischemia/reperfusion group (I/R), PNS 45 mg/kg group (I/R + PNS 45), and PNS 22.5 mg/kg group (I/R + PNS 22.5).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The traditional Chines medicine PNS has been clinically applied as a therapy for cerebrovascular diseases because of its ability to suppress cerebral thrombosis and reduce blood viscosity (Zeng et al, 2014). PNS also exerts neuroprotective effects against CNS ischemia/reperfusion (I/R) injury by reducing inflammation and apoptosis (Ning et al, 2012), as well edema and infarct volume .…”
Section: Discussionmentioning
confidence: 99%
“…Trx-1 has various biological activities and is upregulated in response to a wide variety of stresses, including viral infections and ultraviolet and X-ray irradiation (Masutani et al 2004). Our previous findings showed that Trx-1 played neuroprotective roles in oxidative stress, neurodegenerative disorders, cerebral ischemia, chronic stress, and morphine addiction (Jia et al 2014;Luo et al 2013;Zeng et al 2014a;Zeng et al 2015;Zeng et al 2014b). However, it is unclear whether Trx-1 is involved in acute stress.…”
Section: Introductionmentioning
confidence: 99%